Pemberian Kacang-Kacangan terhadap Perubahan Asam Urat pada Mahasiswi di Asrama Mahasiswa Universitas Muhammadiyah - Sukesih, S; Hidayah, Noor; Ibrizah, Falikhatul (Prosiding University Research Colloquium, 2020)
Nuts are a food source of protein with high nutritional value (20-25 g/ 100 g), vitamin B (thiamin, riboflavin, niacin, folic acid), minerals(Ca, Fe, P, K, Zn, Mg, etc.), and fiber but contain moderate and highpurines, causing uric acid levels in the blood to rise. The purpose ofthis study: to determine the effect of the provision of nuts on goutchanges in students in the Kudus University student dormitory.Research methods: the type of research used is a quasi experiment withthe pretest posttest control group design data analysis using t test, theinstrument of giving nuts using SOP. The population in the study was196 female students sample 32 students with purposive samplingtechnique consisting of 16 female students of the intervention groupand 16 female students of the control group. The results of the studywith paired t test in the intervention group showed that the averagelevel of uric acid prior to treatment was 3.08 mg / dl. after treatment3.83 mg / dl. The mean difference between the before and aftermeasurements is 0.77. The statistical test results obtained 0,000, it canbe concluded that there is a significant difference between uric acidlevels before and after treatment in the intervention group, while theindependent t-test results obtained the average levels of uric acid inthe intervention group who received the treatment of nuts are 3.83 mg/ dl, while for the control group is 3.26 mg / dl. Statistical test resultsobtained p value = 0.016 means that there are significant differencesin the average levels of uric acid in the intervention and control groupsafter treatment.